Motricidad en el desarrollo de las destrezas y habilidades de los estudiantes de primer año de Educación Básica Elemental de la escuela “10 de Noviembre” 2017 - Aspiazu Cevallos, Jessica Marianela (2017)
Currently in the world is living in an era of sedentary children, a time in which the youngest of the home are seen as useless children who are not able to do any work on their own if the help of an adult person, by removing responsibilities of doing some work, the infant is impaired by his psychomotor development, preventing the child from being able to relate, to know and to adapt to the environment that surrounds him. The preschool stage is perhaps the most crucial moment of the child's integral development. At this age, the senses, both external, sight, hearing, touch, smell, taste, and internal, that is to say, those that are activated without direct relation with other objects, are always stimulated and are in the middle of the maturation phase, which requires the directed manipulation of objects to develop their motor skills, stimulate the development of their thinking and the successive learning of more complex skills such as the approach to literacy, and their social development. The psychomotor development of children does not reach an adequate level because psychomotricity is not applied, which is a process of joint development of the mind in coordination with the muscular and the affective, this produces subsequent learning problems and body uncoordination in the different activities daily during the person's life, The development of motor skills is fundamental as a prior process in the initial stage of students to develop their skills and abilities at an early age encourages the student to capture the information quickly stimulating their progress academic. One of the main problems that is evident in the children of the first year of basic education of the school "10 de Noviembre" is that they have difficulty when it comes to fulfilling their tasks in any of the subjects, they do not show creativity they have deficiencies in their learning and in several cases there has been a lack of coordination in the body, resulting in students with low self-esteem isolating themselves from others, which makes it even more difficult to help them